Pharmacology & Pharmacokinetics A Basic Reader - Tomlin, Mark.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Effective drug administration is a crucial skill for any practitioner working in the critical care unit. This book, in providing a concise account of the fundamental principles of pharmacology and pharmacokinetics, equips the critical care physician for such a task. In addition to the principles of pharmacology and pharmacokinetics, this volume alerts the reader to factors that affect drug action such as disease, pregnancy and age, and advises on how to adjust drug dosages accordingly. The specialist therapeutics covered comprise drugs targeting the gastro-intestinal tract, sedation, non-opioid analgesia and opiates. A quick and easy reference, this volume will prove a valuable asset for both trainees and fully qualified practitioners in critical care. Mark Tomlin, BPharm MSc is a consultant pharmacist in critical care at Southampton General Hospital in the UK.
Section I: Pharmacology -- Introduction -- Mechanism of Drug Action -- Pharmacodynamics -- Section II: Pharmacokinetic Principles -- Introduction -- Drug Absorption -- Drug Distribution -- Drug Metabolism -- Drug Excretion -- Factors Affecting Pharmacokinetics -- Drug Interactions with a Pharmacokinetic Basis -- Deciding to Embark on Therapeutic Monitoring -- Summary -- Section III: Introduction to Specialist Therapeutics -- Drugs Targeting the Gastrointestinal Tract in Critical Care -- Sedation on the Intensive Care Unit -- Non-Opoid Analgesia Within the Intensive Care Unit -- Opiates in Critical Care.
Keywords: Medicine; Pharmacy; Critical care medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Pharmacy